2015
DOI: 10.1007/s11814-015-0060-8
|View full text |Cite
|
Sign up to set email alerts
|

Simple boron removal from seawater by using polyols as complexing agents: A computational mechanistic study

Abstract: The complexation of boric acid (B(OH) 3 ), the primary form of aqueous boron at moderate pH, with polyols is proposed and mechanistically studied as an efficient way to improve membrane processes such as reverse osmosis (RO) for removing boron in seawater by increasing the size of aqueous boron compounds. Computational chemistry based on the density functional theory (DFT) was used to manifest the reaction pathways of the complexation of B(OH) 3 with various polyols such as glycerol, xylitol, and mannitol. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…We recently confirmed that the simple addition of polyols (xylitol and mannitol) possessing multiple −OH groups generates larger complexes easily rejected by SWRO membranes, 8 and it was also suggested that the forward reaction is thermodynamically favorable based on the energetics calculated by computational chemistry. 9 Also, Raman spectroscopy indirectly confirmed the preference of B(OH) 3 complex formation with polyols over its conversion into B(OH) 4…”
Section: B(oh)mentioning
confidence: 87%
See 2 more Smart Citations
“…We recently confirmed that the simple addition of polyols (xylitol and mannitol) possessing multiple −OH groups generates larger complexes easily rejected by SWRO membranes, 8 and it was also suggested that the forward reaction is thermodynamically favorable based on the energetics calculated by computational chemistry. 9 Also, Raman spectroscopy indirectly confirmed the preference of B(OH) 3 complex formation with polyols over its conversion into B(OH) 4…”
Section: B(oh)mentioning
confidence: 87%
“…Technically, we emulated PVA polymer, an infinite chain, with an oligomer chain possessing 10 repeating units (see Figure 3Sa in Supporting Information). Then, assuming that the reaction between two neighboring −OH groups of PVA oligomer and B­(OH) 3 releases two water molecules as products, the final geometry of the complex with B­(OH) 3 chemically adsorbed (see Figure 3Sb in Supporting Information) was proposed. The details of the reactions are available in our previous report .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Possible B(OH) 3 -mannitol complexes[20] after the release of one mole of water (left) and two moles of water (right). Red, white, gray and incarnadine balls indicate oxygen, hydrogen, carbon and boron, respectively.…”
mentioning
confidence: 99%
“…이는 수용액 중의 B(OH) 3 가 평형식 (1)을 따르 지 않고 다른 형태의 화학반응에 참여했음을 보여주며 그 반응이 B(OH) 3 과 자일리톨의 착화합물 형성 반응일 수 있다는 것을 간접적 으로 확인해 준다. 이는 이미 선행연구에서 보고되었듯이 계산화학 을 통한 이론적인 가능성과 실험실 수준의 실제 역삼투압 공정 실험 을 통해 얻어진 결과와 서로 상보적으로 연결되고 있다[20,22].…”
unclassified